Cat Stretch Exercise sebagai Salah Satu Solusi Mengatasi Dismenore pada Remaja Putri - Yunita Wulandari; Ika Subekti Wulandari; Atiek Murharyati (Poltekkes Kemenkes Surakarta, 2020)
Background: Dysmenorrhea is a result of menstruation. Dysmenorrhea can cause a variety of complaints in young women such as irregular pain, severe pain and cramps in the lower abdomen that will spread to the back of the back, legs, groin. Cat Stretch Exercise is one of the interventions that is considered to reduce dysmenorrhea pain. The purpose of this study was to determine changes in pain levels in Pondok Imam Bukhari students who were given Cat Stretch Exercise. Methods: The study design used a quasi-two-group pre-test and post-test without control method. Pain measurement with a Numerical Rating Scale (NRS) to assess the level of pain before and after the Cat Stretch Exercise exercise. Respondents in the community service were 31 students who experienced dismenore. Results: Obtained decreased respondents' pain scale from moderate to mild pain. Conclusion: CSE interventions are recommended as one of the non-pharmacological steps to deal with the pain of dysmenorrhea.